Impact of Employee Engagement on Employee Performance in Private Schools in Birendranagar, Surkhet - Irshad Ahmad Iraki (Journal of Nepalese Management and Research, 2024)
Employee engagement is a powerful instrument for organizations to gain a competitive advantage, regardless of size or structure. Engaged employees are acknowledged as invaluable assets and contribute to improved productivity, commitment, and overall performance. This investigation examined the impact of various antecedents of employee engagement on the academic staff of private schools in Birendranagar, Surkhet. The impact of various factors on teacher performance was examined, including work environment, leadership, team and coworker relationships, training and professional development, compensation, organizational policies, and workplace well-being. Employing a positivist perspective, the study embraced a causal-comparative research strategy to explore the relationship between these constructs. After removing extreme outliers, only 389 of the 403 registered responses to the survey were retained for analysis. As revealed by multiple regression analysis, the work environment, training and career development, organizational policies, and workplace well-being significantly influenced teachers' performance. Conversely, compensation, team and coworker relationships, and leadership have insignificant impacts on employee performance. The results of the investigation can be used to establish new policies and programs that are designed to enhance the well-being of teachers. The results of this study provide a comprehensive understanding of the employee engagement factors that significantly influence employee performance in private schools. This information can be used to reinforce or rectify the organization's organizational practices and design features.